Beliefs, motives and gains associated with physical activity in people with osteoarthritis. (5th September 2020) - Berry, Alice; McCabe, Candy S.; Halls, Serena; Muir, Sarah; Walsh, Nicola
Abstract: Objectives: Osteoarthritis (OA) affects approximately 8.75 million people in the United Kingdom. Physical activity is recommended as a core treatment, yet 44% of people with OA are inactive. Motivation and self‐efficacy for exercise are considered to be key factors contributing to sustained engagement with physical activity. The aim of this study was to explore the beliefs, motives (what an individual aims to attain through participating in physical activity) and gains (what people feel they might get from participation) associated with physical activity engagement in a group of people with OA. Design and method: This study adopted a cross‐sectional survey research design, using two validated questionnaires: the Exercise Motives and Gains Inventory and the Exercise Self‐Efficacy Scale. Results: Data were gathered from 262 people with OA between August 2015 and January 2016. Those who were most active reported higher levels of both motivation and self‐efficacy and were active for enjoyment, to avoid negative health, and for health and fitness reasons. A comparison of motives and gains revealed higher gain scores for social engagement and enjoyment, compared with associated motive scores. Conclusion: This study provides evidence of the central role that motives, gains and self‐efficacy play in facilitating engagement with physical activity in this population. Future interventions should aim to foster increased self‐efficacy for physical activity and promote autonomous forms of motivation by emphasising the importance of choosing activities which are enjoyable, as well as highlighting the value of social engagement.